2019
DOI: 10.29252/jafm.12.02.29018
|View full text |Cite
|
Sign up to set email alerts
|

Combined Heat and Mass Transfer during Condensation of Vapours Mixture and Non-Condensable Gas in a Vertical Tube

Abstract: The problem of laminar film condensation from binary vapours mixture with the presence of non-condensable gas (air) flowing in a vertical tube is numerically investigated. The set of the non-linear parabolic equations expressing the mass conservation, momentum, energy, and species diffusion in both phases with the boundary conditions are resolved by using a finite difference numerical scheme. A comparative study between the results obtained for three cases (water-ethanol-air, water-methanol-air, and ethanol-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Ji et al 11 used the steam jet to destroy the mixed boundary layer of steam and NCG, indicating that the steam jet injection can improve the average heat transfer efficiency by about 118%. Charef et al 12 numerically analyzed the condensation from mixed vapors in the presence of the NCG inside a vertical tube. They found that the accumulated condensation rate of water− methanol−air is more enhanced by increasing the mass fraction of the NCG and for a lower wall temperature.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ji et al 11 used the steam jet to destroy the mixed boundary layer of steam and NCG, indicating that the steam jet injection can improve the average heat transfer efficiency by about 118%. Charef et al 12 numerically analyzed the condensation from mixed vapors in the presence of the NCG inside a vertical tube. They found that the accumulated condensation rate of water− methanol−air is more enhanced by increasing the mass fraction of the NCG and for a lower wall temperature.…”
Section: ■ Introductionmentioning
confidence: 99%
“…With the development of surface engineering, hydrophobicity is widely employed to enhance the heat transfer efficiency by removing the condensate more efficiently, where a lot of work is made to realize some special condensate-removal mechanisms, for example coalescence-induced droplet jumping. However, except for the thermal resistance of the accumulated condensate, noncondensable gas (NCG), widely existing in industry, brings significant resistance for the heat transfer process. There have been some investigations focusing on this topic. Tang et al developed theoretical models for film condensation heat transfer with the NCG. Their results present reasonable agreement with the available experimental data.…”
Section: Introductionmentioning
confidence: 99%